Characteristics of wind loads on Twin-Tower structure in comparison with single tower. (15th January 2022) - Qin, Wei-feng; Shi, Jun-yang; Yang, Xiaoyue; Xie, Jiming; Zuo, Steve
Highlights: A twin-tower structure may experience considerably lower wind loads than those on a single isolated tower. The aerodynamic interference between two towers can have a beneficial effect of disrupting regular shedding of vortices, especially for the relative spacing between the two towers smaller than or equal to 1.0. An in-phase and out-of-phase analysis of wind forces can be used in building design to evaluate the effectiveness of structural links for reducing wind response. A case study of 570 m super-tall twin towers verified the above conclusions. Abstract: To provide a general guidance for the wind-resistant design of super-tall twin towers, a study was conducted to investigate the aerodynamic and structural dynamic characteristics of twin towers in comparison with the isolated single tower. It was found that the mutual aerodynamic interference between two towers may have a beneficial effect of disrupting the regular shedding of vortices and causing the across-wind oscillation of the twin towers appreciably smaller than that of the single tower. This beneficial effect is a function of the relative spacing between two towers and the wind direction. When the twin towers are side-by-side to wind, the beneficial effect is apparent if the relative spacing is about 1.0 or less, but it becomes negligible when the relative spacing reaches 2.0. When the twin towers are in tandem configuration to wind, the beneficial effect will remain valid until the maximum tested relative spacing of 2.0. It is also found that wind forces applied to the twin towers may contain a large proportion of out-of-phase components, which act on the two towers in opposite directions, and the corresponding structural response can be well controlled by structural links between the two towers. Therefore, the role and effectiveness of structural links in controlling wind-induced structural responses can be evaluated by the percentage of the out-of-phase components over the total wind forces, which is again a function of the relative spacing, design wind speed, wind direction of concern, and reduced building frequencies. A case study of the 570 m super-tall twin towers verified the conclusions drawn from the general study, and the use of structural links was proved to be able to reduce the design wind loads and building accelerations by more than 20%.